2013
DOI: 10.1007/s10551-013-1708-0
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Performance, Firm Valuation, and Industrial Difference: Evidence from Hong Kong

Abstract: This study addresses two issues. First, does corporate social performance matter in Hong Kong. Second, if yes, is it relevant to some industries more than others. To answer these questions, we develop a corporate social performance index (CSP) to measure the quality of corporate social performance of major Hong Kong listed firms. The criteria are based on the OECD Principles of Corporate Governance. Using the 3-year period from 2002 to 2005, we find that firm valuation is positive and significantly associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 13 publications
1
22
0
6
Order By: Relevance
“…Previous empirical research has also confirmed mixed results regarding the relationship between CSR and FP. The impact of CSR on FP has been found to be positive (Callan & Thomas, 2009;Cheung et al, 2013;Huang & Yang, 2014;Inoue & Lee, 2011;Kong, Liu, & Dai, 2014;Lins, Servaes, & Tamayo, 2017;Lo & Kwan, 2017;Reverte, Gómez-Melero, & Cegarra-Navarro, 2016), negative (Baird et al, 2012;Di Giulia & Kostovetsky, 2014;Lioui & Sharma, 2012;Masulis & Reza, 2015) or insignificant (Soana, 2011;Surroca et al, 2010). Grewatsch and Kleindienst (2017) proposed that the heterogeneity of the linkage between CSR and FP may, to a substantial degree, be explained with some moderators.…”
Section: Csr and Fpmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous empirical research has also confirmed mixed results regarding the relationship between CSR and FP. The impact of CSR on FP has been found to be positive (Callan & Thomas, 2009;Cheung et al, 2013;Huang & Yang, 2014;Inoue & Lee, 2011;Kong, Liu, & Dai, 2014;Lins, Servaes, & Tamayo, 2017;Lo & Kwan, 2017;Reverte, Gómez-Melero, & Cegarra-Navarro, 2016), negative (Baird et al, 2012;Di Giulia & Kostovetsky, 2014;Lioui & Sharma, 2012;Masulis & Reza, 2015) or insignificant (Soana, 2011;Surroca et al, 2010). Grewatsch and Kleindienst (2017) proposed that the heterogeneity of the linkage between CSR and FP may, to a substantial degree, be explained with some moderators.…”
Section: Csr and Fpmentioning
confidence: 99%
“…Moreover, cross‐cultural differences exist between Eastern and Western nations. For instance, the corporate cultures of Western markets have long valued charity activities, but charity activities have yet to see prominence in Asian markets (Cheung, Jiang, Mak, & Tan, ). Wei, Egri, and Lin () also proposed societal differences between Canada and Taiwan in the positive influence of CSR activities on corporate image and employee commitment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of this has focused on how corporations approach CSR in different markets and how their CSR practices are different from Western countries (Welford, , Cheung et al, ). Other areas of CSR research in China have also addressed the effects of CSR on financial performance and brand value (Bouvain et al, ; Cheung et al, ), Chinese stakeholder perceptions of CSR itself or companies' CSR activities (Welford et al, ; Ramasamy & Yeung, ; Wang & Juslin, ), and cultural differences related to CSR (Welford, ; Wong et al, ). When it comes to evaluating companies' CSR, Chinese consumers tend to care less about discerning companies' motives and care more about results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research on CSR has also identified differences between mainland China and Hong Kong. Positive CSR effects on market value were more evident among companies listed in Hong Kong, but such effects were found to be weaker among mainland Chinese‐related companies (Cheung et al, ). This is not surprising given Hong Kong's distinct political, economic, and social development characteristics (Welford, ).…”
Section: Literature Reviewmentioning
confidence: 99%